Editor's Choice – Randomised Clinical Trial of Supervised Exercise Therapy vs. Endovascular Revascularisation for Intermittent Claudication Caused by Iliac Artery Obstruction: The SUPER study. (March 2022) - Koelemay, Mark J.W.; van Reijen, Nick S.; van Dieren, Susan; Frans, Franceline A.; Vermeulen, Erik J.G.; Buscher, Hessel C.J.L.; Reekers, Jim A.; ,; Dijkgraaf, M.G.W.; de Haan, R.J.; Balm, R.; Idu, M.M.; et al.
Abstract : Objective: International guidelines recommend supervised exercise therapy (SET) as primary treatment for all patients with intermittent claudication (IC), yet primary endovascular revascularisation (ER) might be more effective in patients with iliac artery obstruction. Methods: This was a multicentre RCT including patients with IC caused by iliac artery stenosis or occlusion (NCT01385774). Patients were allocated randomly to SET or ER stratified for maximum walking distance (MWD) and concomitant SFA disease. Primary endpoints were MWD on a treadmill (3.2 km/h, 10% incline) and disease specific quality of life (VascuQol) after one year. Additional interventions during a mean follow up of 5.5 years were recorded. Results: Between November 2010 and May 2015, 114 patients were allocated to SET, and 126 to ER. The trial was terminated prematurely after 240 patients were included. Compliance with SET was 57/114 (50%) after six months. Ten patients allocated to ER (8%) did not receive this intervention. One year follow up was complete for 90/114 (79%) SET patients and for 104/126 (83%) ER patients. The mean MWD improved from 187 to 561 m in SET patients and from 196 to 574 m in ER patients ( p  = .69). VascuQol sumscore improved from 4.24 to 5.58 in SET patients, and from 4.28 to 5.88 in ER patients ( p  = .048). Some 33/114 (29%) SET patients had an ER within one year, and 2/114 (2%) surgical revascularisation (SR). Some 10/126 (8%) ER patients had additional ER within one year and 10/126 (8%) SR. After a mean of 5.5 years, 49% of SET patients and 27% of ER patients underwent an additional intervention for IC. Conclusion: Taking into account the many limitations of the SUPER study, both a strategy of primary SET and primary ER improve MWD on a treadmill and disease specific Qol of patients with IC caused by an iliac artery obstruction. It seems reasonable to start with SET in these patients and accept a 30% failure rate, which, of course, must be discussed with the patient. Patients continue to have interventions beyond one year.